PIPELINE GAME IN THE CASPIAN REGION - S. S. Zhiltsov (Проблемы постсоветского пространства)
The breakdown of the USSR was followed by appearance of new independent states on the Caspian for which the development of new hydrocarbon deposits and their export to foreign markets opened new horizons of development. This paper investigates the results of pipeline rivalry in the Caspian region that started after the USSR disintegration.